Societal disintegration in Northern-Ireland - fact or fiction - Heskin, K (Economic & Social Studies, 1981)
Within the framework of these results there was indication of the growing importance of electrical and mechanical skills and improvements in labour productivity in changing the basis of Irish trade.It has been suggested by politicians, journalists and researchers that, as a result of the prolonged civil conflict in Northern Ireland, societal norms and values may have been seriously eroded and that the future may be bleak for Northern Irish society, whatever happens politically. This hypothesis is tested using levels of indictable crime as an index of such social disintegration. Comparisons of, and predictions from, levels of indictable crime in Northern Ireland, the Republic of Ireland and England and Wales are made. Similar analyses are conducted on the cities of Belfast and Dublin. No evidence emerges to support the hypothesis.
Keywords: Economics; Sociology